miRNAs Participate in MS Pathological Processes and Its Therapeutic Response - Ting Wu; Guangjie Chen (Mediators of Inflammation)
Multiple sclerosis is the most common autoimmune disease of the central nervous system. It is believed that the increased migration of autoreactive lymphocytes across the blood-brain barrier (BBB) may be responsible for axonal demyelination of neurons. In this review, we discuss microRNAs participating in the pathological processes of MS, including periphery inflammation, blood-brain barrier disruption, and CNS lesions, and in its therapeutic response, in order to find biomarkers of disease severity and to predict the response to therapy of the diseases.